Gambaran Kualitas Layanan Kesehatan di Puskesmas Ngemplak Simongan - Putri, Rita Amelia; Kusumo, Wahyu Eko Giri; Desty, Rani Tiara (Universitas Ivet, 2023)
Service quality is one measure to assess public services. Public service is an activity or a series of activities in the context of fulfilling service needs in accordance with statutory regulations for every citizen and resident for goods, services and/or administrative services provided by public service providers. The state is obliged to serve every citizen and resident to fulfill their basic rights and needs within the framework of public services which are mandated by the 1945 Constitution. The Ngemplak Simongan Health Center is the first level implementing unit in providing health services in its working area, namely the village level. The purpose of this study was to see the extent to which the quality of health services at the Ngemplak Simongan Health Center was satisfied by looking at the elements of safety, effectiveness, patient-centered, timely, efficiency, fairness. The method used in this research is purposive sampling. The results showed that the health services at the Ngemplak Simongan Health Center were quite good, but there were still some that were lacking at this Health Center. It is hoped that the facilities and infrastructure available at the Ngemplak Simongan Health Center can improve the performance and quality of services provided. It is hoped that the Ngemplak Simongan Health Center can be better in providing services in the future by seeing that there is still dissatisfaction with health service users at the Ngemplak Simongan Health Center.